(3GdLhGH GdcGaj def SCd Yf GdOhGA GdTGaj (B/ s - (3GHf bje GdLhRjI, eMeO Hf CHj HcQ Hf CjhH, (B691-751 (3gLQj eDda(B.s; (3TYjH , eMeO jhfS (B- (3eMbbs; (3GdMQSJGfj , YUGe aGQS (B- (3eMbbs ((3YeGf, GdCQOf (B: s (3OGQ YeGQ, s, 1991)
(3gh cJGH Cdag GdEeGe GHf bje GdLhRjI (B(691(3g` (B- 751(3g`(B). (3jJfGhd aj aUhdg ehVhY EUdGM GdfaS hJbhjegG, hJgPjHgG hab GdefXhQ GdESdGej, MjK jJfbd GdbGQjA Hjf aUhdg eGQkG HGdfUjMI hGdJhHjN, hjYGdL GdcJGH BaGJ GdfaS GdCeGQI HGdShA, eXgQG YjhHgG hRdGJgG, heHjfkG SdWI GdTghGJ YdjgG, heMPQkG ef ecGjO GdTjWGf hMjdg aj EjbGY GdfaS HGdeYGUj hGdPfhH, hGdQchf ddMjGI GdOfjG hRjfJgG(B.s
Keywords: (3Yde GdfaS GdESdGejs